2016
DOI: 10.1002/jsfa.7676
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the production and economic benefits from preventing cows grazing on wet soils in New Zealand

Abstract: Deferring dairy cow grazing from wet Pallic soils in North Otago was effective in improving soil structure (measured as total soil porosity), yet did not lead to a significant increase in pasture production. Whole farm modelling indicated no economic benefit of removing cows from wet soils during the milking season. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
0
8
0
Order By: Relevance
“…Similarly, Beukes et al (2013) concluded in a modeling study that 6-to 8-h access to pasture per day under conditions conducive to treading damage was more profitable than keeping cows indoors completely. The 2 main differences between the present study and previous modeling studies of whole-farm scenarios (Beukes et al, 2013;Laurenson et al, 2016Laurenson et al, , 2017 are that (1) previous studies used a modeling approach with an assumed decreasing pasture production as a function of stocking density and access time to pasture when animals were turned out during wet soil conditions, and (2) capital costs increased when cows were taken off during wet soil conditions (completely or temporarily). However, those studies were conducted in New Zealand, under the premise that standoff facilities had to be purpose-built for holding cows off pasture.…”
Section: Effect Of Grazing System On Profitabilitymentioning
confidence: 85%
See 3 more Smart Citations
“…Similarly, Beukes et al (2013) concluded in a modeling study that 6-to 8-h access to pasture per day under conditions conducive to treading damage was more profitable than keeping cows indoors completely. The 2 main differences between the present study and previous modeling studies of whole-farm scenarios (Beukes et al, 2013;Laurenson et al, 2016Laurenson et al, , 2017 are that (1) previous studies used a modeling approach with an assumed decreasing pasture production as a function of stocking density and access time to pasture when animals were turned out during wet soil conditions, and (2) capital costs increased when cows were taken off during wet soil conditions (completely or temporarily). However, those studies were conducted in New Zealand, under the premise that standoff facilities had to be purpose-built for holding cows off pasture.…”
Section: Effect Of Grazing System On Profitabilitymentioning
confidence: 85%
“…Likewise, in the present study, net profit was lowest in the control system due to a combination of higher costs and lower milk sales. Laurenson et al (2016) modeled the effects of restricting access of dairy cows to pasture and reported higher costs when cows were taken off compared with turned out to pasture during wet soil conditions. The difference was primarily due to higher feed costs.…”
Section: Effect Of Grazing System On Profitabilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Off-paddock facilities can be used to reduce N returns to pasture during periods of low N utilisation and in turn decrease the risk of N leaching in winter and spring [23]. In addition, off-paddock facilities protect wet pasture from treading damage [24,25].…”
Section: Introductionmentioning
confidence: 99%